Association of climate variability with hepatitis A and E infections in Dhaka (2016–2023) (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Acute viral hepatitis, predominantly caused by hepatitis A virus (HAV) and hepatitis E virus (HEV), remains a major global public health issue, especially in low- and middle-income countries. This study was conducted to determine the prevalence of acute hepatitis A and E infections in Dhaka city and to examine the influence of weather conditions on their transmission.Methods: This retrospective study, based on laboratory data, was conducted at the Department of Virology, Bangladesh Medical University from 2016 to 2023. It analysed the test results for anti-HAV-IgM and anti-HEV-IgM antibodies from blood specimens of suspected acute hepatitis cases. The patients’ details and laboratory results were retrieved using the Laboratory Information System, and climatic variables (temperature, humidity, and rainfall) were obtained from the Bangladesh Meteorological Department.Results: In this study, test reports from 19,542 individuals for HAV and 23,249 individuals for HEV were analysed. HAV was detected in 29.5% of the population, and HEV was found in 20.6%. Males were predominantly seropositive for both HAV (65.1%) and HEV (76%). HAV was most common in those aged ≤10 and 11–20 years (37.9%), whereas HEV was most common in the 21–30 years group (40.6%). Higher HAV transmission was observed during autumn and late autumn, while HEV was more prevalent in summer and the rainy season.Conclusion: Acute HAV and HEV infections are common in Dhaka city, and climatic factors affect their spread. Understanding these patterns can improve public health readiness and raise awareness of social health hygiene.